Characterisation of 99mTc EDDA/HYNIC-TOC (Tektrotyd) physiological and neuroendocrine tumour uptake using SPECT/CT standardised uptake values: initial experience. Issue 8 (August 2021) - Reilly, Caitlin; Gemmell, Alastair J.; McLaughlin, Ian M; Fleming, Robert; Reed, Nicholas; McIntosh, David; Nicol, Alice
Abstract : 99m Tc Ethylene diamine N, N '-diacetic acid hydrazinonicotinamide-conjugated Tyr 3 -octreotide ( 99m Tc EDDA/HYNIC-TOC) single photon emission tomography/computed tomography (SPECT/CT) imaging of somatostatin receptors is used in the assessment of neuroendocrine tumours (NETs). The objective of this study was to characterise quantitative standardised uptake value (SUV) SPECT/CT of normal physiological uptake and NET disease. Forty-four patients (22 female and 22 male) referred for 99m Tc EDDA/HYNIC-TOC SPECT/CT imaging for diagnosis/primary staging ( n  = 28) or the assessment of residual/recurrent disease ( n  = 16) were included. SPECT/CT SUVmax values were determined for normal physiological uptake (spleen, kidney, liver and bone) and NET disease (liver metastases, metastatic lymph nodes, bone metastases and intrapulmonary lesions). Statistical testing was performed to compare normal uptake and NET disease uptake in liver and bone (Student's t -test). The highest normal physiological uptake was observed in the spleen (mean SUVmax 29.8, SD 13.7), with lower uptake in the kidneys (16.7, 3.2) and liver (7.3, 2.1). Increased SUVmax values were observed in primary tumour and metastatic disease, greatest in liver metastases (21.8, 13.3), with lower, similar values obtained for metastatic lymph nodes (16.3, 7.5) and intrapulmonary lesions (17.5, 16.8). SUVmax in bone metastases averaged 12.9 (7.0). Significant differences were observed between normal and metastatic SUVmax in the liver and bone ( P  < 0.01). SPECT/CT SUV quantification is feasible in a manner similar to PET/CT. 99m Tc EDDA/HYNIC-TOC SPECT/CT SUVmax has been characterised in NET disease, demonstrating high target to non-target ratios for primary tumours and metastatic lesions.